Fabrication and assessment of bifunctional electrospun poly(L-lactic acid) scaffolds with bioglass and zinc oxide nanoparticles for bone tissue engineering - Canales, Daniel A.; Piñones, Natalia; Saavedra, Marcela; Loyo, Carlos; Palza, Humberto; Peponi, Laura; Leonés, Adrián; Baier, Raúl Vallejos; Boccaccini, Aldo R.; Grünewald, Alina; Zapata, Paula A. (International Journal of Biological Macromolecules, 2023)
Electrospun scaffolds based on poly(L-lactic acid) (PLLA) with bioglass (n-BG) and zinc oxide (n-ZnO), and mixture of both, were developed to design bifunctional biomaterials with enhanced bioactive and biocidal properties. The presence of n-BG increased the fiber diameter of the pure PLA from 1.5 ± 0.3 μm to 3.0 ± 0.8 μm for 20 wt%. ZnO and the mixed nanoparticles did not significantly affect the morphology. The mechanical properties decreased with the presence of nanoparticles. Scaffolds based on PLA/n-BG promoted hydroxyapatite (HA) formation in simulated body fluid (SBF) that was inhibited with the presence of ZnO. Notably, mixed particles produced bioactivity although at longer times. The incorporation of n-ZnO produced a biocidal capacity against S. aureus in the polymeric scaffold, reaching a viability reduction of 60 % after 6 h of exposure. When both types of nanoparticles were combined, the bacterial viability reduction was 30 %. Pure PLA scaffolds and the composites with n-BG showed good ST-2 bone marrow-derived cell line viability, scaffolds with n-BG (pure or mixture) presented lower viability. Results validated the use of both n-BG and n-ZnO fillers for the development of novel bifunctional PLA-based scaffolds with both bioactive and biocidal properties for bone tissue engineering applications.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Bioglass nanoparticle; Bone tissue engineering; Electrospun fibers; Functional scaffolds; Poly(lactic acid) based nanocomposites; Zinc oxide nanoparticle